Effects of foundation flexibility on elastic and inelastic seismic responses of multi-story buildings - Mission, Jose Leo C.; Pennung Warnitchai; Barry, William Joseph; Noppadol Phien-Wej; Asian Development Bank - Japan Scholarship Program (ADB - JSP) (Pathum Thani, Thailand : Asian Institute of Technology, 2005)
A procedure for evaluating the effects of foundation flexibility on the seismic responses of a 9-story and 15-story slab-column frame buildings on pile foundation was presented using a coupled soil-pile-structure interaction model with multi-support earthquake excitation. The analysis was coupled, that is, the structure and pile foundation were integrated into one model and analyzed in one analysis step. The analysis was two-dimensional and other modeling and analysis procedures were also presented such as the method of using elastic spring stiffness coefficients at the supports with uniform excitation. A method for evaluating the lateral stiffness coefficients of the foundations was also presented in this study using the coupled soil-pilestructure model. Results were evaluated and compared with a structure model analyzed using a fixed and rigid base. Results have shown that a flexible foundation has the general effect of increasing the natural period of the structure and alters the natural mode shapes. There was no clear trend on the variation of the increase or decrease of the base shear and base moment for the buildings being studied. In general, the variation of the increase of the story shear and story bending moment is higher in the lower floors and diminishing towards the upper floors. The same pattern was also observed in the lateral story displacements wherein there was a greater increase in the lateral story displacements at the lower floors and a decreasing variation with increasing height. For the two multi-story buildings being studied, the variation of the increase in story shear and story bending moment compared to that of a fixed base model is more pronounced in the 9-story building with only a slight variation of the response in the 15-story building. A significant feature presented in the coupled soil-pile-stricture model used in this study was the ability to monitor pile global forces and displacements which are relevant in foundation design. The principal conclusion in this study is that soil-pile-structure interaction may affect significantly the dynamic response of structures and must, in general be considered in design
A thesis submitted in partial fulfillment of the requirements for the degree of Master of Engineering, School of Engineering and Technology
Thesis (M.Eng.) - Asian Institute of Technology, 2005
Keywords: Foundations; Buildings -- Earthquake effects